2016
DOI: 10.1590/1809-2950/15988723042016
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms in different severity degrees of bruxism: a cross-sectional study

Abstract: | Objective: The aim of the present study was to evaluate symptoms of the muscle pain, sleep quality, oral health, anxiety, stress and depression in individuals with different severity degrees of bruxism. Methods: Seventytwo individuals with bruxism were enrolled in the study, classified into: moderate (n=25) and severe (n=47) bruxism.Pain intensity was assessed using the Visual Analogical However, both present similarity in stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
1
0
5
Order By: Relevance
“…An epidemiological study developed in Italy with individuals 18 to 75 years of age found an association between back pain and bruxism (Ciancaglini et al, 2001). Another study conducted in Brazil with individuals 18 to 60 years of age concluded that the pain caused by bruxism occurs not only in the masticatory muscles, but also in the craniofacial complex and neck (Amorim et al, 2016). The neurofunctional and anatomic interactions among the skull, temporomandibular joint, and cervical spine may clarify this association.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological study developed in Italy with individuals 18 to 75 years of age found an association between back pain and bruxism (Ciancaglini et al, 2001). Another study conducted in Brazil with individuals 18 to 60 years of age concluded that the pain caused by bruxism occurs not only in the masticatory muscles, but also in the craniofacial complex and neck (Amorim et al, 2016). The neurofunctional and anatomic interactions among the skull, temporomandibular joint, and cervical spine may clarify this association.…”
Section: Discussionmentioning
confidence: 99%
“…Encontramos al bruxismo como origen de patologías dentales y periodontales, y relacionado con desordenes temporomandibulares (DTM), ya sean artropatías o miopatías (Magnusson, 2005). En este contexto, Santos et al (2016) Así mismo, se pueden presentar otros síntomas de gran importancia que incluso pueden llegar a generar incapacidad médica de vuelo, como son:…”
Section: Clínicaunclassified
“…De modo consequente, o bruxismo pode provocar dor nos músculos cervicais e mastigatórios, também dores de cabeça, que podem diminuir os limiares de tolerância de dor nas regiões orofacial e cervical e, desta maneira, alterar a qualidade da saúde bucal e do sono, além de aumentar o estresse, ansiedade e depressão. 4 A busca pelos cirurgiões-dentistas para realizar a investigação do hábito parafuncional tem ocorrido com bastante periodicidade. Nesse sentido, o diagnóstico deve ser feito por meio de exame clínico e anamnese minuciosa; nesta, analisam-se as questões psicológicas do paciente e, na avaliação clínica, observam-se os desgastes dentários.…”
Section: Introductionunclassified